2017
DOI: 10.1063/1.4986010
|View full text |Cite
|
Sign up to set email alerts
|

Raman three-wave interaction in partially spin polarized plasma

Abstract: By employing the separate spin evolution-quantum hydrodynamic model (SSE-QHD), the nonlinear growth rate of the parametric decay instability is studied via the Raman scattering process of three-wave coupling. SSE-QHD equations are solved for the pump wave (O-mode), sideband Shear Alfvén wave, and the electron plasma perturbations. It is observed that the spectrum of the electron plasma waves is modified due to newly generated spin dependent waves which contribute in the coupling process. The nonlinear growth r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
7
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 24 publications
(7 citation statements)
references
References 52 publications
0
7
0
Order By: Relevance
“…The Raman threewave interaction for the pump wave (O-mode), sideband Shear Alfven wave, and the electron plasma perturbations, is considered in terms SSE-QHD equations. It is found that the nonlinear growth rate is suppressed due to the spin effects [24]. Ion-acoustic shock wave propagation in dense magnetized plasmas with relative density effects of spin-up and spin-down degenerate electrons is studied in Ref.…”
Section: Introductionmentioning
confidence: 99%
“…The Raman threewave interaction for the pump wave (O-mode), sideband Shear Alfven wave, and the electron plasma perturbations, is considered in terms SSE-QHD equations. It is found that the nonlinear growth rate is suppressed due to the spin effects [24]. Ion-acoustic shock wave propagation in dense magnetized plasmas with relative density effects of spin-up and spin-down degenerate electrons is studied in Ref.…”
Section: Introductionmentioning
confidence: 99%
“…Our main purpose is to investigate the effect of the SRS on the spin dynamics in the case of a polarized electron plasma. A similar problem was studied recently using a hydrodynamic approach [42].…”
Section: Stimulated Raman Scatteringmentioning
confidence: 97%
“…Majority of application of the separate spin evolution quantum hydrodynamics (SSE-QHDs) is related to the spin-electron acoustic waves (SEAWs). However, there are papers devoted to the influence of the separate spin evolution and the spin polarized Fermi pressure on the following phenomena: Raman three-wave interaction for the pump wave (O-mode), sideband Shear Alfven wave, and the electron * Electronic address: andreevpa@physics.msu.ru plasma perturbations [33], and non-linear propagation of ion-acoustic waves [34].…”
Section: Introductionmentioning
confidence: 99%